Application of the Salp Swarm Algorithm to Optimal Design of Tuned Inductive Choke - Knypiński, Łukasz; Kurzawa, Milena; Wojciechowski, Rafał; Gwóźdź, Michał (Energies (Basel), 2024)
The article presents an algorithm and optimization software designed for the optimal configuration of a tuned inductive choke. The optimization software consists of two main parts: an optimization procedure and a mathematical model for the designed electromagnetic devices. A lumped-parameters model of a tuned inductive choke was developed, with the device’s structure described by three design variables. As an optimality criterion, the multi-objective compromise function was adopted. The objective function merges the total inductances of the electromagnetic device under different operation states. The optimized structure was analyzed using the finite element method. The developed lumped-parameters model is characterized by good accuracy and can be successfully applied to optimize tuned inductive chokes for various rated parameters. The optimization procedure was adapted to the tuned inductive choke model by appropriately selecting the characteristic coefficient of the salp swarm algorithm. The reliability of the optimization software was verified through experimental measurements.